Long-term change in healthy food consumption in Finland during 1985-2016: An age-period-cohort analysis - Kähäri Antti (International Sociological Association (ISA), 2022)
Societal change is reflected in food consumption habits. In postindustrial societies consumers are increasingly emphasizing health, ethical, and ecological aspects in their consumption habits. This study investigated the changes in food consumption in Finland during 1985-2016. Fruits and berries, vegetables, and fish were used as indicators of healthy and contemporary food habits. To untangle the dynamics of change, time series data of Finnish household budget surveys from 1985 to 2016 and novel age-period-cohort models were used. The share of total food expenditure of all examined foods increased during the study period. Increasing vegetable and fruit consumption was reflected in the younger birth cohorts consuming more than the preceding ones. The food expenditure shares of fruit, berries, and fish were highest and rose most in over-50 age groups. However, the food expenditure shares of vegetables, and fruit and berries also rose in younger age groups during the most recent period. Cohort differences could not be explained by rising incomes, educational level or urbanization.